Status of visual impairment among indigenous (Orang Asli) school children in Malaysia - Omar, Rokiah; Wan Abdul, Wan Mohd Hafidz; Knight, Victor Feizal (BMC public health, 2019)
Background School children are considered a high-risk group for visual impairment because uncorrected refractive errors and problems such as amblyopia can seriously affect their learning abilities and their physical and mental development. There are many studies reporting the prevalence of refractive errors among school children of different ethnic groups in Malaysia, however, studies concerning the prevalence of refractive errors among indigenous or Orang Asli children are very limited. Therefore, the objective of this study was to determine the prevalence and causes of visual impairment among Orang Asli children. Methods One hundred ten Orang Asli children aged 7 to 12 years old in Negeri Sembilan, Malaysia were selected. 51% of these children were boys while the remainders were girls. They underwent visual acuity test, cover test, Hirschberg’s test, ocular external assessment and ophthalmoscopy. Children who failed the vision screening were then referred for further eye examination. Results Of these 110 Orang Asli children, 46 failed the vision screening and subsequently 45 of them were confirmed to have visual problems (40.9% of the total subjects). The main cause of visual impairment in this study was refractive error (34.5% of the total subjects) where the main refractive error found was hyperopia (28.2%) followed by amblyopia (2.7%), strabismus (1.8%) and ocular abnormalities (1.8%). Conclusion Hence, vision screening and a comprehensive eye examination is very important and needs to be done on all Orang Asli children so that any visual problems can be detect at an early stage to avoid the development of learning difficulties among these already disadvantaged children.